Partituren der Städte. Urbanes Bewusstsein und musikalischer Ausdruck. - (:unkn) unknown (transcript, 2015)
Das Design und die Entzifferung des Urbanen vollziehen sich zugleich auf multiplen Ebenen sozialer Konfigurationen und künstlerischer Wahrnehmung. Stadt ist somit way of life, Projektionsfläche, Image und imaginärer Lebensraum, der seit dem 19. und 20. Jh. eines der zentralen programmatischen Motive in Literatur, Malerei, Film und Musik bildet. Im Zentrum stehen ausdrücklich musikalische Deutungen. Die Beiträge geben Einblick in die Vielfältigkeit künstlerischer Stadterfindungen und untersuchen anhand unterschiedlicher Metropolen-Porträts differenzierte Reaktionen auf das Städtische, Optiken und Ausdrucksformen sowie die Vergangenheit und Gegenwart urbaner Imaginationen.

By drawing together widely dispersed yet central writings, the Berlin Reader is an essential resource for everyone interested in urban development in one of the most interesting and important metropolises in Europe. It provides scholars as well as students, journalists and visitors with an overview of the most central discussions on the tremendous changes Berlin experienced since the fall of the wall. It covers a wide range of issues, including inner city renewal, housing and the local economy, gentrification and other urban conflicts. The book breaks ground in two dimensions: first, by offering also non-German speakers an insight into the very controversial debates after reunification, and, second, by highlighting the ambivalent consequences of Berlin's urban transformation in the past decades.
Keywords: Stadtsoziologie; Urbanität; Design; Musik; Stadtbild; Reflexion; Bewusstsein; Polyphonie